OPTIMALISASI TEMPERATUR AIR PADA MORTAR RIGID PAVEMENT DENGAN PASIR SUNGAI (QUARRY TEMPUR)TERHADAP KUAT TEKAN DAN KUAT LENTUR - Yayan Adi Saputro (Universitas PGRI Semarang, 2021)
In general, especially the construction of rigid pavement construction uses building materials with good quality to obtain the desired quality, for example using vomit sand instead of river sand. Even though Jepara area has a lot of river sand which can be used as compiler material for development, especially the construction of rigid pavement. Mixing planning is the main thing that must be known to get good results, planning a mixture is the key to producing good quality concrete. Therefore it is necessary to study Jepara sand quarry on water temperature for rigid pavement by conducting pressure test and flexural test. The purpose of this research is to study jepara quarry sand (Tempur) which has the best characteristics between the three and know the temperature / temperature of the water produces the highest compressive strength and flexural strength for site mix work in rigid pavement. The temperature / temperature used is 18º C, 27º C, 36º C, 45º C. Based on the research results obtained that the combat sand quarry, the original mud content of 15.38%, organic content of brownish yellow NaOH color, granular modulus of fineness of 3.08, specific gravity of 2.03, absorption of 29.88%. The optimum temperature that obtained the highest compressive strength was quarry sand powder with a temperature / water temperature of 18º C that is at 7 days of 226 Kg / cm2, 14 days of age of 247.9 Kg / cm2, and 28 days of 266 Kg / cm2 and at the age of 28 days it has a flexural strength of 1.85 MPa..